Nervous gastritis due to post-traumatic stress in Mangalarga Paulista foal: Case report - Daneze, Edmilson Rodrigo [UNESP]; De Toledo, Carmen Zilda Pereira [UNESP]; Maia, Ricardo Silva; Da Rosa Sobreira, Márcia Ferreira [UNESP] (Medicina Veterinaria (UFRPE), 2022)
Gastritis is characterized by inflammation of the gastric mucosa and may be a process triggered by stressful situations. Thus, the present study aims to report the case of a Mangalarga Paulista foal attended with suspicion of acute abdomen initiated approximately one hour after heavy rain. During physical examination, no abnormalities of motility, positioning or content were detected, however, great sensitivity was observed in the region of the xiphoid process on intestinal auscultation, rectal palpation and gastric lavage. After administering an antacid, the foal was placed in a paddock along with its mother and remained stable until the following morning, when it was separated for the halter work, becoming quite stressed. In the afternoon of the same day, he presented a new acute abdomen crisis. On suspicion of stress gastritis, gastric secretion inhibitor, motility stimulant and antacid were prescribed, and it was recommended to avoid consecutive stressful activities until complete recovery of the patient. After two years of care, the animal did not present new episodes of acute abdomen.
Gastrite nervosa decorrente de estresse pós-traumático em potro Mangalarga Paulista: Relato de caso
Keywords: Abdomen acute; Dressage; Rain; Stress; Weaning